REVIEW OF THE IMPLEMENTATION OF TRI HITA KARANA-BASED SUSTAINABLE TOURISM IN MONKEY FOREST, PADANGTEGAL VILLAGE, UBUD DISTRICT, GIANYAR REGENCY - Ni Putu Nita Purwasih; Ni Nyoman Perni; I Made Gede Anadhi (UHN IGB Sugriwa Denpasar, 2024)
Pariwisata is a type of activity that quietly enlightens and educates the public, hence offering various benefits to the local community. The crucial role of pariwisata in the development of economies across many nations has not been overlooked. Due to this, Bali is expected to be able to launch the pariwisata's potential in an ideal manner. Furthermore, as a precursor to the aforementioned pariwisata development, it was included in Undang Undang No. 10 of 2009. The Fifth Amendment on the 2020 Standard Penyelenggaraan Kepariwisataan Bali. Through the implementation of the Tri Hita Karana concept, which is a Hindu religious warisan in Monkey Forest Desa Padangtegal Kecamatan Ubud, Kabupaten Gianyar, a unique and respectful environment will be created for each visitor to the area. This study identifies three problems: 1) the implementation of the pariwisata's kelanjutan program at Monkey Forest Desa Padangtegal Kecamatan Ubud, 2) the implementation of the pariwisata's kelanjutan program at Monkey Forest Desa Padangtegal Kecamatan Ubud, and 3) the implications of the review of the implementation of the pariwisata's kelanjutan program based on Tri Hita Karana in Monkey Forest Desa Padangtegal Kecamatan Ubud. The three problems above are explained using two theories: 1) The Pariwisata Growth Theory and 2) The Pariwisata Fallacy Theory. This study employs a deskriptif kualitatif approach by utilizing the bidding process of education and religious organizations. The research results obtained state that the implementation of sustainable tourism in the Monkey Forest, Padangtegal Village, Ubud District, Gianyar Regency, includes Ecological Sustainability, Cultural Sustainability and Economic Sustainability. Application of Tri Hita Karana in Sustainable Tourism in Monkey Forest, Padangtegal Village, Ubud District, Gianyar Regency, including Parahyangan, Pawongan, and Pabelasan. The implications of the Review of the Implementation of Sustainable Tourism Based on Tri Hita Karana in Monkey Forest, Padangtegal Village, Ubud District, include 1) Environmental Balance, 2) Welfare and Role of Local Communities, 3) Cultural Harmony, 4) Respect for Spirituality, 5) Partnership between Parties which are involved.